LIFE CYCLE DATA ANALYSIS FOR SMART CITIES AND SUPPORT WITH GEOGRAPHIC INFORMATION SYSTEM (GIS) - Kocalar, A. C. (ISPRS annals of the photogrammetry, remote sensing and spatial information sciences, 2017)
The dynamics of globalization have gained momentum with today's developing technology. So we are now faced with the problems of urbanization (and urban governance), which become more evident than in the old days. As the subject cities, interdisciplinary qualities must always be considered. In the study, too, the focus of the urban area was on the problematic issue of intelligent or smart (especially, transportation) management that remained within this framework. GIS plays a major role in establishing the relationship between all kinds of analyses and visual information in the same environment and in determining the right strategies. For this reason, the use of GIS for decision makers is one of the most commonly used methods for intellectual production in the smart cities concept. The work to be done with this method will be able to be systematically successful and sustainable applications in this way.